Mandatory labelling of Nanofoods and the WTO agreements - Hasmin, Nor Akhmal; Zainol, Zinatul Ashiqin; Azizun, Najwa; Abd Kadir, Nur Hafidah (Universiti Utara Malaysia Press, 2020)
The labelling of food products that contain new technologies have been carried out to ensure that consumers are well informed on the hazards and uncertainty of the technologies incorporated for food production. Although food labelling is important, the implementation of mandatory labelling measures for nanofood within the domestic legislation is only possible if it is aligned with the regulations of the World Trade Organisation (WTO). This study examines the mandatory labelling measure for nanofood that would be permissible under the WTO agreements, i.e. under the Technical Barriers to Trade Agreement and the Sanitary and Phytosanitary Agreement. This study adopted a doctrinal approach and content analysis that examine the relevant legal provisions in the WTO agreements, proceedings conducted by the WTO, and other documents on nanofood labelling. The findings suggest that the labelling measure amounts to unnecessary barriers to international trade. Moreover, mandatory labelling is not an international labelling standard, while the practice of mandatory labelling was found to be trade restrictive. Some recommendations were presented in this study that provide valuable insights on the implementation of mandatory labelling for nanofood if countries decide to introduce this measures into their food information system.